A Multisite Preregistered Paradigmatic Test of the Ego-Depletion Effect. (October 2021) - Vohs, Kathleen D.; Schmeichel, Brandon J.; Lohmann, Sophie; Gronau, Quentin F.; Finley, Anna J.; Ainsworth, Sarah E.; Alquist, Jessica L.; Baker, Michael D.; Brizi, Ambra; Bunyi, Angelica; Butschek, Grant J.; Campbell, Collier; et al.
We conducted a preregistered multilaboratory project ( k = 36; N = 3, 531) to assess the size and robustness of ego-depletion effects using a novel replication method, termed the paradigmatic replication approach . Each laboratory implemented one of two procedures that was intended to manipulate self-control and tested performance on a subsequent measure of self-control. Confirmatory tests found a nonsignificant result ( d = 0.06). Confirmatory Bayesian meta-analyses using an informed-prior hypothesis (δ = 0.30, SD = 0.15) found that the data were 4 times more likely under the null than the alternative hypothesis. Hence, preregistered analyses did not find evidence for a depletion effect. Exploratory analyses on the full sample (i.e., ignoring exclusion criteria) found a statistically significant effect ( d = 0.08); Bayesian analyses showed that the data were about equally likely under the null and informed-prior hypotheses. Exploratory moderator tests suggested that the depletion effect was larger for participants who reported more fatigue but was not moderated by trait self-control, willpower beliefs, or action orientation.